Epigenome-Wide Association Study Identifies Cardiac Gene Patterning and a Novel Class of Biomarkers for Heart Failure. Issue 16 (17th October 2017) - Meder, Benjamin; Haas, Jan; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Frese, Karen; Lai, Alan; Nietsch, Rouven; Scheiner, Christina; Mester, Stefan; Bordalo, Diana Martins; Amr, Ali; Dietrich, Carsten; et al.
Abstract : Background: Biochemical DNA modification resembles a crucial regulatory layer among genetic information, environmental factors, and the transcriptome. To identify epigenetic susceptibility regions and novel biomarkers linked to myocardial dysfunction and heart failure, we performed the first multi-omics study in myocardial tissue and blood of patients with dilated cardiomyopathy and controls. Methods: Infinium human methylation 450 was used for high-density epigenome-wide mapping of DNA methylation in left-ventricular biopsies and whole peripheral blood of living probands. RNA deep sequencing was performed on the same samples in parallel. Whole-genome sequencing of all patients allowed exclusion of promiscuous genotype-induced methylation calls. Results: In the screening stage, we detected 59 epigenetic loci that are significantly associated with dilated cardiomyopathy (false discovery corrected P ⩽0.05), with 3 of them reaching epigenome-wide significance at P ⩽5×10 −8 . Twenty-seven (46%) of these loci could be replicated in independent cohorts, underlining the role of epigenetic regulation of key cardiac transcription regulators. Using a staged multi-omics study design, we link a subset of 517 epigenetic loci with dilated cardiomyopathy and cardiac gene expression. Furthermore, we identified distinct epigenetic methylation patterns that are conserved across tissues, rendering these CpGs novel epigenetic biomarkers for heart failure. Conclusions: The present study provides to our knowledge the first epigenome-wide association study in living patients with heart failure using a multi-omics approach. Abstract : Supplemental Digital Content is available in the text.